Country Versus Industry Diversifications In Asean And Their Determinants - Lee, Meng Horng (2013)
This study examines the role of common, country and industry effects in international diversification potential in ASEAN stock markets. This study follows Heston & Rouwenhorst (1994) decomposition approach in extracting these effects from stock returns. Given the increased integration of financial markets and previous mixed findings, ongoing debates of country versus industry diversifications are still remain unsolved. The first stage analysis will scrutinize whether country or industry diversification is more fruitful and the evolutions of common, country and industry effects throughout the sample period. The second stage analysis of this study focuses on the determinants of country and industry effects, where it could provide better understanding towards the driving forces behind the magnitude of country and industry effects. Specifically, panel regressions are employed in the second stage analysis. The sample of this study comprises 4043 individual firms across ASEAN countries classified using the industry classification benchmark (ICB) over the period 1990-2010.